Strategi Konten Instagram Dalam Meningkatkan Kesadaran Merek Museum Sonobudoyo Yogyakarta - Annisa Bella Novita , Sari; Widhihatmini, Widhihatmini; Utomo, Ardian Setio; Utari, Tituk; Warhamni, Dewi (Jurnal Pekommas, 2023)
The role of museums in the digital era is no longer directed at collections but towards 'Edutainment' (Educational Entertainment) which keeps up with the times by providing information and communication in visual form via Instagram. There are various ways that can be done in preserving culture, but the most important thing is how to raise awareness and a sense of belonging to love the culture itself, so that people will continue to be motivated to learn about it. The existence of the Sonobudoyo Museum in Instagram is expected to provide positive attractive insight to the community. This research is conducted to find out the Instagram content strategy carried out by the Sonobudoyo Museum in increasing brand awareness for the community. The type of research used is qualitative research with a descriptive analysis approach, that interprets the data with words or descriptions. The data collection techniques use the method of observation, interviews and documentation. The results of the study show that the content strategy for the Instagram @sonobudoyo account is implemented consistently. The strategies undertaken include context, communication, collaboration and connection. Brand awareness analysis contained in the @sonobudoyo account involves several elements, namely being different, meaningful, transferability, adaptability, and publicity. The advantage of this journal is the idea and concept of the authors who examine museum attractions with relevant theoretical approaches, supporting references, systematic descriptions, and easy-to-understand explanations.